Post-Purchase Consumer Behavior; Factors and Their Importance - Bahiroh, Eloh; Rismawati, Rismawati; Rizky, Yasmine Diva (PT FORMOSA CENDEKIA GLOBAL, 2024)
Post-purchase consumer behavior is a natural reaction of customers to the goods they buy, usually post-purchase consumer behavior is very spontaneous according to the state of the product and the tastes of the consumers themselves. Post-purchase consumer behavior is strongly motivated by product quality according to consumer vision glasses, post-purchase consumer behavior is able to influence product management decisions and is able to influence other customers. The research methodology used by the author is descriptive qualitative with the data collection technique is literature study, the range of materials obtained by the author is quite wide but the author experiences limitations in the sample. There are three factors that influence post-purchase consumer behavior, including satisfaction, completeness and service. So, the subjects in marketing will improve their techniques and coordinate with other divisions. The last is an example of consumer behavior in the form of a review, a review is a statement about something that is stated based on aspects of the product without being influenced by other things, in the sense that the review needs to be done according to the actual situation to avoid any disadvantaged parties.